Afro-Brazilians : cultural production in a racial democracy - Afolabi, Niyi (Rochester studies in African history and the diaspora., 2009)
In this absorbing new study, Niyi Afolabi exposes the tensions between the official position on racial harmony and the reality of marginalization experienced by Afro-Brazilians by exploring Afro-Brazilian cultural production as a considered response to this exclusion. The author examines major contributions in music, history, literature, film, and popular culture in the nineteenth and twentieth centuries to reveal how each performance by an Afro-Brazilian artist addresses issues of identity and racism through a variety of veils that entertain, ridicule, invoke, provoke, protest, and demand change at the same time. Raising cogent questions such as the vital role of Afro-Brazilians in the making of Brazilian national identity; the representation of Brazilian women as hapless, exploited, and abandoned; the erosion of the influence of black movements due to fragmentation and internal disharmony; and the portrayal of Afro-Brazilians on the national screen as domestics, Afolabi provides insightful, nuanced analyses that tease out the complexities of the dilemma in their appropriate historical, political, and social contexts. Niyi Afolabi teaches Luso-Brazilian, Yoruba, and African Diaspora studies in the Department of Spanish and Portuguese as well as the John L. Warfield Center for African and African American Studies at the University of Texas at Austin.